Pembentukan Polis dan Migrasi Subjek Tokoh Oshin dalam Film Oshin Karya Shin Togashi (Kajian Sosiologi Sastra Perspektif Jacques Ranciere) - Priventa, Hendrike; Handayani, Umi; Riani, Rosalina Wahyu (Vocational College of Diponegoro University, 2023)
Abstract This study addresses the topic of policy formation and subject migration in Shin Togashi's Oshin film. The purpose of this study was to 1) describe the formation of policies, and 2) describe the migration of Oshin character subjects. The approach used is literary sociology with Ranciere's perspective. The results of this study show that there are three policies, namely, 1) policies in the family environment, 2) policies in the work environment, and 3) policies in the surrounding community. The results regarding subject migration are as follows. Oshin figures experience five migration processes namely, 1) subjects as children to workers, 2) subjects as workers to younger siblings, 3) subjects as younger siblings to children, 4) subjects as children to workers and children, 5) subjects as workers and children to children.